Chiral Room Temperature Ionic Liquids as Enantioselective Promoters for the Asymmetric Aldol Reaction. Issue 24 (17th July 2014) - González, Laura; Escorihuela, Jorge; Altava, Belén; Burguete, M. Isabel; Luis, Santiago V.
Abstract: Chiral ionic liquids derived from natural amino acids are shown to be green and efficient media for direct asymmetric aldol reactions at room temperature catalyzed by ( S )‐proline. The corresponding aldol products were obtained with moderate to good enantioselectivities. A transfer of chirality from the chiral reaction media has been observed as well as the participation of match/mismatch interactions of the chiral medium with both enantiomers of proline. Moreover, these catalytic systems were easily recovered by simple filtration, and studies on their reuse have demonstrated that recycling is possible for at least four runs with only a slight reduction in activity. Abstract : Chiral ionic liquids derived from natural amino acids are shown to be efficient solvents or additives for direct asymmetric aldol reactions. A match/mismatch effect between the configuration of the chiral ionic liquid and that of proline has been observed, with a higher enantioselectivity obtained for the ( S )‐proline/CIL2 complex.